Creating diversity markets through economization: The politics and economics of difference in neoliberal organizations. Issue 2 (23rd April 2021) - Arciniega, Luzilda C.
Abstract : In this article, I argue that the economization of social differences in the workplace is a political practice. I examine how, after the dismantling of corporate bureaucracies and affirmative action policies, diversity professionals create economic justifications for practices they regard as creating racial equity. Insofar as they do this to conveniently create markets for their expertise, diversity professionals work with, through, and around neoliberal logics, principles, and norms of the for‐profit firm. In asking why their strategies "work" in the era of the socially dispersed corporate form, I reflect on what it means for an American society to place more social value on the pursuit of profit than on racial justice.